Bioinformatic Screening of Compounds from Iranian Lamiaceae Family Members against SARS-CoV-2 Spike Protein - Alibakhshi, Abbas; Gharibi, Shima; Ahangarzadeh, Shahrzad; Yarian, Fatemeh (Letters in Drug Design & Discovery, 2023)
Background: COVID-19 (coronavirus disease 2019) is still a major challenge worldwide. The disease is caused by binding the coronavirus to ACE2 receptors on lung cells, infecting the cells and triggering the onset of symptoms. The prevention of such a binding in which the virus is eventually unable to enter the cell could be a promising therapeutic approach. Methods: In this in silico study, 306 compounds of Lamiaceae family native in Iran (native Mints) were retrieved from several databases as 3D structures, and after that molecular docking and virtual screening, the compounds with inhibitory potential were selected in terms of free energy binding against the spike protein of the virus. The pharmacokinetic profile of selected compounds was evaluated, and by molecular dynamic simulation and MM/PBSA, four compounds were further assessed for binding affinities against the receptor-binding domain of the spike. Results: The results showed the Catechin gallate and Perovskone B from Stachys and Salvia genus generated a stronger binding affinity, and therefore could act as potential inhibitory compounds of RBD of the SARS-CoV-2 spike protein. Conclusion: This study revealed that some members of the Lamiaceae family could be employed to inhibit SARS-CoV-2 activity through interaction with spike protein and therefore could be used for further investigation in vitro and in vivo.
Keywords: molecular docking